Microfinance for change: how financial innovation enables structural transformation - Shankar Ghimire; Bharat Singh Thapa; Rong Zheng (Financial Innovation)
Abstract This study examines the influence of microfinance institutions’ (MFIs) financial innovation on structural transformation. For this purpose, we considered a household survey from Nepal. The survey collected data on various individual and household characteristics, borrowing patterns, and occupations over the years. The key question focused on occupations before and after borrowing, a categorical response variable indicating 1 for occupational change after borrowing and 0 otherwise. Therefore, we use logistic regression to estimate the probability of occupational change, given two measures of financial innovation: loan purpose and size. The results show that the number of households involved in agriculture significantly decreased, with the majority switching to businesses and convenience stores, indicating a shift to the manufacturing and service sectors. These findings suggest that MFIs contribute to local-level structural transformation by enabling borrowers to move away from traditional employment. This study has important implications for policymakers, development practitioners, and academics interested in promoting economic development through microfinancing in low-income countries.